Privacy and Identity Management: Time for a Revolution? : 10th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, Edinburgh, UK, August 16-21, 2015, Revised Selected Papers - Aspinall, David; Camenisch, Jan; Hansen, Marit; Fischer-Hubner, Simone; Raab, Charles (Privacy and Identity Management. Time for a Revolution? 10th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, Edinburgh, UK, August 16-21, 2015, Revised Selected Papers, 2016)
This book contains a range of keynote papers and submitted papers presented at the 10th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, held in Edinburgh, UK, in August 2015. The 14 revised full papers included in this volume were carefully selected from a total of 43 submissions and were subject to a two-step review process. In addition, the volume contains 4 invited keynote papers. The papers cover a wide range of topics: cloud computing, privacy-enhancing technologies, accountability, measuring privacy and understanding risks, the future of privacy and data protection regulation, the US privacy perspective, privacy and security, the PRISMS Decision System, engineering privacy, cryptography, surveillance, identity management, the European General Data Protection Regulation framework, communicating privacy issues to the general population, smart technologies, technology users' privacy preferences, sensitive applications, collaboration between humans and machines, and privacy and ethics.